On Anti-paremias of the Covid-19 Period in Lithuanian and Latvian - Liparte, Evija; Zavistanavičienė, Daiva (Tautosakos darbai, 2026)
The article explores anti-paremias in Lithuanian and Latvian that reflect Covid-19 pandemic realities and people’s attitudes towards them. The term anti-paremia is perceived here as purposeful transformation of traditional paremias, i.e. proverbial phrases, proverbs, aphorisms, sententious utterances, phraseologisms, and quotations of literary origin. The study’s empirical material was collected from online written texts and images including official social advertising campaigns and anti-paremias created by individuals. Anti-paremias here are examined based on two aspects: in accordance with types of paremia transformation (substitution of one/several words or parts of a sentence, supplementation, reduction, cross-contamination of several paremias following the classification of the Polish scientist Anna Gabryel, applied to the analysis of German anti-proverbs of the Covid-19 pandemic period); and according to semantic grouping of anti-paremias in Covid-19 pandemic narratives. Many researchers follow similar classifications, whereas this study is based specifically on Gabryel’s model. The most common anti-paremia transformation method in both languages was substitution (35 % of the Lithuanian sample and 73 % of the Latvian sample). Semantic group analysis revealed that human behaviour-related anti-paremias dominate in Lithuanian (47 %) whereas in Latvian vaccination-themed paremias were most frequent (57 %). This reflects the time when these anti-paremias were created. The lowest number of witty transformations were immunity-related, with only one example in Lithuanian, and none in Latvian.